Chile : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper examines economic developments in Chile during 1995-97. Average output growth exceeded 7 percent in 1995-97 and twelve-month inflation fell from 9 percent at end-1994 to 6 percent at end-1997. Economic management during this period was complicated by a sharp swing in export prices, and-up to the last quarter of 1997-strong and rising capital inflows. After a surge in 1995, the price of copper declined by more than 20 percent in 1996, recovered in early 1997, and fell sharply later in the year.